Multifrequency Pulsed EPR Studies of Biologically Relevant Manganese(II) Complexes - Stich, T. A. (2007)
Electron paramagnetic resonance studies at multiple frequencies (MF EPR) can provide detailed electronic structure descriptions of unpaired electrons in organic radicals, inorganic complexes, and metalloenzymes. Analysis of these properties aids in the assignment of the chemical environment surrounding the paramagnet and provides mechanistic insight into the chemical reactions in which these systems take part. Herein, we present results from pulsed EPR studies performed at three different frequencies (9, 31, and 130 GHz) on [Mn(II)(H(2)O)(6)](2+), Mn(II) adducts with the nucleotides ATP and GMP, and the Mn(II)-bound form of the hammerhead ribozyme (MnHH). Through line shape analysis and interpretation of the zero-field splitting values derived from successful simulations of the corresponding continuous-wave and field-swept echo-detected spectra, these data are used to exemplify the ability of the MF EPR approach in distinguishing the nature of the first ligand sphere. A survey of recent results from pulsed EPR, as well as pulsed electron-nuclear double resonance and electron spin echo envelope modulation spectroscopic studies applied to Mn(II)-dependent systems, is also presented.